2009
DOI: 10.1093/molehr/gap034
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase expression in human cumulus oophorus cells

Abstract: Success in assisted reproductive techniques (ART) is influenced by gamete and embryo quality but the assessment of these parameters has been thwarted by the lack of reliable biomarkers. Follicular fluid and cumulus oophorus cells may provide biomarkers due to their close relationship to the oocyte. These cells produce antioxidants and thus protect the oocyte from oxidative damage exerted by reactive oxygen species (ROS). ROS and antioxidants are known to intervene in reproductive physiology and pathology, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 46 publications
4
90
0
1
Order By: Relevance
“…The correlation between patients' age and log2 expression values for genes related to oxidation-reduction process, regardless of therapy, is not statistically significant. A negative correlation between age and gene expression of genes involved in defense against reactive oxygen species (ROS) in follicles is well known and has been reported in several studies [28][29][30][31]. It seems that in our study we have controlled this effect by including patients of similar age and younger than 35 years, which is proved by a non-significant correlation (Table S3-Regardless of therapy).…”
Section: Discussionmentioning
confidence: 86%
“…The correlation between patients' age and log2 expression values for genes related to oxidation-reduction process, regardless of therapy, is not statistically significant. A negative correlation between age and gene expression of genes involved in defense against reactive oxygen species (ROS) in follicles is well known and has been reported in several studies [28][29][30][31]. It seems that in our study we have controlled this effect by including patients of similar age and younger than 35 years, which is proved by a non-significant correlation (Table S3-Regardless of therapy).…”
Section: Discussionmentioning
confidence: 86%
“…Data of a recently published study showed that SOD activity decreased with age in women, but increased in women with endometriosis and ovulatory dysfunction (Matos et al, 2009). When the cause of infertility was male factor, the success of ART was associated with increased SOD activity.…”
Section: Enzymatic Antioxidantsmentioning
confidence: 93%
“…When the cause of infertility was male factor, the success of ART was associated with increased SOD activity. Variations in SOD activity emphasize the importance of oxidative stress in the oocyte maturation process, and are suggested to be a potential biomarker of ART success (Matos et al, 2009).…”
Section: Enzymatic Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the significant downregulation of MnSOD in previously vitrified day-5 blastocysts from obese mice may be caused by decompensation to stress. Superoxide dismutase (SOD) activity has been shown to diminish with increasing female age, and successful ART was associated with higher SOD activity [47]. This implies that day-5 blastocysts previously vitrified on day 3 in the obese group are still in a stressed state.…”
Section: The Effect Of Obesity On Vitrificationmentioning
confidence: 99%